Research on subsystem division scheme of overlapping decentralized control strategy - Qinghu Xu; Xiang Ruan; Xuezhi Zhen; Yuntong Dai; Xiaofang Kang; Jun Hu (Systems Science & Control Engineering, 2022)
The overlapping decentralized control strategy is a solution to the decentralized control of large-scale systems based on the inclusion principle. Its design process can be summarized as three stages of expansion-decoupling-contraction. In this paper, the subsystem division scheme of the overlapping decentralized control strategy is studied for building structure systems under earthquake. Using the energy-to-peak algorithm, we mainly analyse the influences of the location of the overlapping layer, the number of overlapping layers and the number of subsystems on the control effect of the structural system, and compare them with the traditional energy-to-peak centralized control method. The numerical results indicate that the dynamic response of the structure can be effectively suppressed by raising the location of the overlapping layer, increasing the number of overlapping layers, and increasing the number of subsystems. Compared with the centralized control strategy, the control effect is equivalent, or even better, verifying the feasibility of this research scheme.